Easy synthesis of photoluminescent N-doped carbon dots from winter melon for bio-imaging. Issue 40 (1st April 2015) - Feng, Xin; Jiang, Yaoquan; Zhao, Jingpeng; Miao, Miao; Cao, Shaomei; Fang, Jianhui; Shi, Liyi
Abstract : An edible winter melon was utilized both as a carbon source and a nitrogen source to synthesise photoluminescent N-doped CDs 4.5–5.2 nm in size through an efficient one-step hydrothermal method. Abstract : N-doped carbon dots were successfully synthesized via a one-step hydrothermal method by using edible winter melon as the source material. Mono-dispersed CDs 4.5–5.2 nm in diameter were achieved in a quantum yield (QY) of 7.51%. The photoluminescent CDs were demonstrated to be effective bio-imaging agents for hepG2 (liver hepatocellular carcinoma) cells.